2017
DOI: 10.1200/jco.2017.35.15_suppl.11051
|View full text |Cite
|
Sign up to set email alerts
|

Administration of aldoxorubicin and 14 days continuous infusion of ifosfamide/mesna in metastatic or locally advanced sarcomas.

Abstract: 11051 Background: Aldoxorubicin (A) has demonstrated superior anti-tumor efficacy and lack of cumulative cardiac toxicity in multiple studies. A is doxorubicin (D) with a linker which rapidly binds in vivo to albumin after iv. We studied the combination of A administered on Day 1 with continuous infusion (CI) of ifosfamide/Mesna (I-M) days 1-14, as first line therapy or second line therapy in patients with soft tissue sarcomas (STS) to evaluate efficacy and toxicity. Methods: 27 patients have entered the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Aldoxorubicin has also demonstrated tolerability and activity in combination with other chemotherapy agents in STS; in one study, aldoxorubicin was combined with doxorubicin with no DLTs and additional cardiotoxicity observed. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldoxorubicin has also demonstrated tolerability and activity in combination with other chemotherapy agents in STS; in one study, aldoxorubicin was combined with doxorubicin with no DLTs and additional cardiotoxicity observed. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…A separate open-label, Phase I study demonstrated that aldoxorubicin can also be administered safely with other chemotherapy agents commonly used in the treatment of STS. 35 Here, aldoxorubicin administered at 250 mg/m 2 on day 1 with continuous infusion of ifosfamide and mesna (1 g/m 2 each per day up to 14 days for a maximum of 6 28-day cycles) in 27 patients with STS in the first- or second-line settings showed promising ORR with the most common AE being myelosuppression ( Table 1 ). There were 10 patients with PR or SD who had subsequent surgery to remove accessible tumors.…”
Section: Phase I Trialsmentioning
confidence: 92%
“…In another Phase II study, sarcoma patients received therapy with ALDOX at 170 mg/m 2 (125 mg/m 2 DE; n=7) or 250 mg/m 2 (185 mg/m 2 DE; n=38) on day 1 and IFOS at 1 g/m 2 /day on days 1–14 of a 28-day cycle. 72 , 73 The combination was given up to six cycles, but ALDOX could continue thereafter as monotherapy. Prominent toxicities included myelosuppession, nausea/vomiting, stomatitis, and febrile neutropenia.…”
Section: Efficacy Studies Of Aldox In the Management Of Stssmentioning
confidence: 99%
“…A recently published report showed that the median progression-free survival (PFS) was, respectively, 8.2 months and 4.8 months with objective response rates (ORRs) of 19.5% and 25.6% for AI and ADM (7). Additionally, single-arm data have also indicated the feasibility and tolerability of AI (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%